2022
DOI: 10.1038/s43018-022-00383-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting PARP11 to avert immunosuppression and improve CAR T therapy in solid tumors

Abstract: Evasion of anti-tumor immunity and resistance to therapies in solid tumors are aided by immune-suppressive tumor microenvironment (TME). We found that TME factors such as regulatory T cells and adenosine downregulated type I interferons (IFN1) receptor IFNAR1 on CD8 + cytotoxic T lymphocytes (CTL). These events relied upon poly-ADP ribose polymerase-11 (PARP11), which was induced in the intratumoral CTL and acted as a key regulator of the immune suppressive TME. Ablation of PARP11 preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Autologous CAR T cell products for hematological cancers have had an impressive impact on patients who had previously failed other conventional therapy approaches 16 . The initial success with CD19 + cancers has shown the potential of engineered immune oncology cell therapeutics and there is hope that new immune cell products will be successful in treating other types of cancer as well [17][18][19] . However, even for hematological malignancies, such as diffuse large B-cell lymphoma or multiple myeloma for which there are approved autologous CAR T products, supply currently falls short of the demand, demonstrating the unmet medical need for patients who cannot access autologous CAR T therapies 20 .…”
Section: Discussionmentioning
confidence: 99%
“…Autologous CAR T cell products for hematological cancers have had an impressive impact on patients who had previously failed other conventional therapy approaches 16 . The initial success with CD19 + cancers has shown the potential of engineered immune oncology cell therapeutics and there is hope that new immune cell products will be successful in treating other types of cancer as well [17][18][19] . However, even for hematological malignancies, such as diffuse large B-cell lymphoma or multiple myeloma for which there are approved autologous CAR T products, supply currently falls short of the demand, demonstrating the unmet medical need for patients who cannot access autologous CAR T therapies 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of various gene engineering techniques can modulate T cell activation and proliferation and have resistance to inhibitory signals from the tumor microenvironment. For example, when combined with CAR technology, knocking out immune checkpoint inhibitors, such as CTLA4, PD1 or PARP11 [197], further improves the ability of CAR T cells to traffic to and infiltrate tumors, where overcoming the immunosuppressive microenvironment represents a prime challenge [198,199]. Allogeneic T cells from healthy donors or derived from induced pluripotent stem cells (iPSC) were successfully generated, and demonstrated high preclinical efficacy [200,201] and many clinical trials with allogenic CAR T cells are already underway (https:// clini caltr ials.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies have further demonstrated the promise of integrating multi-dimensional omics data to understand the determinants of CAR T cell efficacy. For example, the efficacy of CAR T cells can be enhanced through the inhibition of key immunosuppressive factor in the tumour microenvironment (TME), 8 and the composition of bacterial species of gut microbiome was also associated with the response to CAR T therapy. 9 Finally, we summarized the factors related to CAR T cell-induced toxicities revealed by muti-omics data.…”
Section: Cart Omicsmentioning
confidence: 99%